DETERMINATION OF VITAMIN C IN SEVERAL VARIETIES OF MELON FRUITS BY TITRATION METHOD - Nerdy Nerdy (Universitas Syiah Kuala, 2017)
Abstract. Vitamin C (ascorbic acid) is micronutrient that is water soluble and indispensable for the body's metabolism, also plays a role in immune function. Vitamin C are easy to be absorbed actively. One of the fruits that contain vitamin C is melon fruit. Many varieties of melon fruit affect the vitamin C levels. The levels of vitamin C can be determined by 2,6-dichloroindophenol titration method using 2,6-dichloroindophenol solution. The advantages of the 2,6-dichloroindophenol titration method in the determination of vitamin C levels is reductor substances other than vitamin C are not oxidized by 2,6-dichloroindophenol. The examination begins with the determination of equivalence of 2,6-dichloroindophenol solution to vitamin C and followed by determination of vitamin C levels in several varieties of melon fruit. Equivalence of 2,6-dichloroindophenol solution to vitamin C was obtained 0,1347 mg vitamin C per 1 mL 2,6-dichloroindophenol solution. Levels of vitamin C in various varieties of melon fruit obtained that the highest levels was in Golden Melon variety (9,209 mg vitamin C per 100 g of Golden Melon) while the lowest levels was in Langkawi Melon variety (0,335 mg of vitamin C per 100 g of Langkawi Melon). It can be concluded that vitamin C levels contained in melon fruit vary and depend on melon fruit varieties.Keywords: Vitamin C, Ascorbic Acid, Melon Fruits, Varieties, Titration MethodREFERENCE S. Almatsier, 2001, Prinsip Dasar Ilmu Gizi, Gramedia Pustaka Utama, Jakarta, 152-153, 185-186.F. Prajnanta, 2003, Melon: Pemeliharaan secara Intensif dan Kiat Sukses Beragribisnis. Penebar Swadaya, Jakarta, 3, 30.R. Rukmana, 2007, Melon Hibrida, Kanisius, Yogyakarta, 11, 13-15, 16.B. Samadi, 2007, Melon: Usaha Tani dan Penanganan Pascapanen, Kanisius, Yogyakarta, 19, 23, 25-28, 31.P.M. Wijoyo, 2009, Panduan Praktis Budi Daya Melon, Bee Media Indonesia, Jakarta, 14-17, 55.I.G. Gandjar, dan A. Rohman, 2007, Kimia Farmasi Analisis, Pustaka Pelajar, Yogyakarta, 249.N. Andarwulan, dan S. Koswara, 1992, Kimia Vitamin, Rajawali Press, Bogor, 14-20, 32-35, 235.Direktorat Jenderal Pengawasan Obat dan Makanan Departemen Kesehatan Republik Indonesia, 1995, Farmakope Indonesia, Edisi Ke-4, Departemen Kesehatan Republik Indonesia, Jakarta, 1215-1216.W. Horwitz, 2002, Official Methods of Analysis of Association Offical Analytical Chemist Internasional, Edisi Ke-42, Association Offical Analytical Chemist International Suite, Maryland, 16-17.10. J.N. Counsell, and D.H. Hornig, 1981, Vitamin C, Applied Science Publisher, London, 123-124.11. R.M. Astrid, 2016, Cara Cerdas Berkebun Emas Dengan Menanam Melon, Villam Media, Depok, 67.